2015
DOI: 10.1097/md.0000000000000749
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Embolization for Ruptured Ectopic Bronchial Artery Aneurysm

Abstract: Bronchial artery aneurysm (BAA) is an uncommon disease, and spontaneous rupture of an ectopic BAA can be difficult for diagnosis and life-threatening. This case study describes a 52-year-old man who presented with acute onset of right chest pain, mild tachycardia, and hypertension. The initial diagnosis of acute myocardial infarction was made, and the patient was given nitroglycerin prior to admission to our hospital. However, the patient's symptoms deteriorated. An enhanced computed tomography scan revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
3
0
4
Order By: Relevance
“…An 17 examples of spontaneous rupture of the branches of LSA in patients including ours (Table 1 ), have been reported in the literature. [ 4 18 ] The most common clinical feature of rupture was pain (70.6%, 12/17) with the position of chest, back, and neck, others included sensory deficit (23.5%, 4/17), expanding mass (17.6%, 3/17), dyspnea (17.6%, 3/17), stridor (11.8%, 2/17), hae- mothorax (11.8%, 2/17), and dysphagia (5.9%, 1/17). Among these 17 patients, we found that spontaneous rupture was happened with congenital or acquired vascular anomalies of the aortic arch, comprised of aberrant LSA itself, such as aneurysms (58.8%, 10/17), right aortic arch (RAA) (17.6%, 3/17), aortic dissection (11.8%, 2/17), and aortic coarctation (5.9%, 1/17).10 of 17 patients with von Recklinghausen's disease (VRD) (neurofibromatosis) had rupture of LSA, which was considered as mainly hereditary disease that was at risk of rupturing of LSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An 17 examples of spontaneous rupture of the branches of LSA in patients including ours (Table 1 ), have been reported in the literature. [ 4 18 ] The most common clinical feature of rupture was pain (70.6%, 12/17) with the position of chest, back, and neck, others included sensory deficit (23.5%, 4/17), expanding mass (17.6%, 3/17), dyspnea (17.6%, 3/17), stridor (11.8%, 2/17), hae- mothorax (11.8%, 2/17), and dysphagia (5.9%, 1/17). Among these 17 patients, we found that spontaneous rupture was happened with congenital or acquired vascular anomalies of the aortic arch, comprised of aberrant LSA itself, such as aneurysms (58.8%, 10/17), right aortic arch (RAA) (17.6%, 3/17), aortic dissection (11.8%, 2/17), and aortic coarctation (5.9%, 1/17).10 of 17 patients with von Recklinghausen's disease (VRD) (neurofibromatosis) had rupture of LSA, which was considered as mainly hereditary disease that was at risk of rupturing of LSA.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually associated with primary diseases such as congenital, or acquired vascular anomalies, trauma, tumor, hypertension (HBP). [ 2 18 ] Here we reported a case of spontaneous rupture of the branches of left subclavian artery (LSA) and the patient recovered well by the timely treatments.…”
Section: Introductionmentioning
confidence: 99%
“…TAE was employed in our case with the aim to totally occlude the aneurysm and tortuous bronchial arteries. All sorts of embolic materials have been successfully used in clinical practices, such as detachable coils, gelatin sponges, or N -butyl cyanoacrylate [12] . Among these, coils are most commonly used to treat BAA.…”
Section: Discussionmentioning
confidence: 99%
“…종격동혈종은 대부분 외상, 흉부 대동맥류 혹은 대동맥박리 파열, 종격동 종양의 출혈이 일반적인 원인이며, 드물게 기관지동맥류의 파열 혹은 기관지동맥의 박리가 원인일 수 있다( 8 ). 기관지동맥류는 결핵, 기관지확장증과 같은 만성적인 기관지 및 폐실질의 염증과 관련이 깊다( 8 9 10 ). 폐혈관에 혈관수축, 혈전, 혈관염이 발생하게 되고 폐세동맥 수준에서 폐순환이 감소하여 이에 대한 보상으로 기관지동맥으로의 동맥혈이 증가하게 된다.…”
Section: 고찰unclassified
“…폐혈관에 혈관수축, 혈전, 혈관염이 발생하게 되고 폐세동맥 수준에서 폐순환이 감소하여 이에 대한 보상으로 기관지동맥으로의 동맥혈이 증가하게 된다. 이로 인해 기관지동맥의 직경이 확장되고 부분적으로 동맥류를 형성할 수 있다( 8 10 ). 본 증례의 경우, 색전술 후 영상에서 NBCA가 결절형으로 캐스팅되어 있는 소견을 볼 때 기저에 기관지동맥류가 있었을 가능성이 있다.…”
Section: 고찰unclassified